Usaha Meningkatkan Hasil Belajar Siswa dengan Mengimplementasikan Model Discovery Learning pada Hasil Belajar Matematika Kelas VI A di SDN 1 Kekeri - M. Valian Aji Sukma; Mukayati; Yunita Arian Sani Anwar (Mataram University, 2026)
This study aimed to improve students’ academic achievement through the implementation of the discovery learning model. The application of this model provides students with direct learning experiences by engaging them in experimental activities that facilitate the independent discovery of mathematical concepts and principles. The research problem focused on how the implementation of discovery learning could enhance mathematics learning achievement of Grade VI A students at SDN 1 Kekeri. This study described the implementation of the discovery learning model in improving students’ mathematics learning outcomes. The research employed Classroom Action Research (CAR) involving Grade VI A students of SDN 1 Kekeri, Gunung Sari District, West Lombok Regency. The data analysis revealed that students’ learning activities at the classical level reached 61.86% in Cycle I and increased to 74.99% in Cycle II. Furthermore, students’ learning achievement showed a significant improvement of 30.30%, increasing from 60.60% in Cycle I to 90.90% in Cycle II. Based on these results, it can be concluded that the implementation of the discovery learning model effectively improved students’ mathematics learning outcomes and achieved learning mastery.